1978
DOI: 10.1128/iai.20.2.541-551.1978
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic analysis of coccidioidin and spherulin determined by two-dimensional immunoelectrophoresis

Abstract: MATERLALS AND METHODSAntigen preparations. Coccidioidin was prepared by the toluene lysis method published previously (13, 25) but with the following modification. After lysis of the fungus mat with toluene-saturated distilled water, the filter-sterilized lysate was lyophilized, removing the toluene, and then dissolved with the original broth 541 on August 8, 2020 by guest http://iai.asm.org/ Downloaded from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 29 publications
3
53
0
Order By: Relevance
“…Comparison of the intermediate-gel IEP plates in Fig. 4C and D demonstrated that the rabbit antiserum raised against the OG-SF of SOW contained antibodies against antigens 2 and CS of the reference system (4,14,19).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Comparison of the intermediate-gel IEP plates in Fig. 4C and D demonstrated that the rabbit antiserum raised against the OG-SF of SOW contained antibodies against antigens 2 and CS of the reference system (4,14,19).…”
Section: Resultsmentioning
confidence: 94%
“…56,1988 on August 5, 2020 by guest http://iai.asm.org/ Downloaded from was analyzed in our earlier investigations (4, 5) by twodimensional immunoelectrophoresis (IEP). The coccidioidin (CDN)-anti-CDN reference system used for identification of specific antigens was originally developed by Huppert and co-workers (14,19) and has been reproduced in our laboratory with anticoccidioidin obtained from newly immunized burros. The procedure used for IEP examination in this study involved preparation of an intermediate gel (22) composed of 1 part rabbit serum (either preimmune serum or antiserum raised against OG-SF) to 1 part 2% agarose.…”
mentioning
confidence: 99%
“…Quantitative and q been reported in stu INFECT. IMMUN. etween Histoplasma and mycelia and yeast (or spherule) phases of these etween Histoplasma and three dimorphic fungi (10,18,19). Recently, trast to blastomycin KCB-Huppert et al (19) demonstrated 26 protein-1) did not elicit cross-reac-containing bands in coccidioidin (XV) using two--reactive subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Antigens. Antigens from the saprophytic and parasitic (tissue) phases of C. immitis, H. capsulatum, and B. dermatitidis differ qualitatively and quantitatively (10,18,19). For this reason, LT assays were performed with antigens derived from mycelial and yeast (or spherule) phases of the three fungi.…”
mentioning
confidence: 99%
“…MATERIALS AND METHODS Antigen preparations. Coccidioidin was prepared as described previously (9). Briefly, 12 isolates of C. immitis were grown separately in 2% glucose-1% yeast extract dialysate broth on a rotary shaker at 30 to 330C.…”
mentioning
confidence: 99%